O efeito de concussões recorrentes associadas à prática de exercício físico de natação na comunicação entre cérebro, baço e intestino de ratos - Godinho, Douglas Buchmann (2021)
Traumatic Brain Injury (TBI) is defined as an alteration in brain function caused by a force external to the brain, and 80 to 90% of cases are mild TBI or concussion. As for the TBI damage mechanism, it is divided into primary damage, which is the moment of mechanical insult to the brain, and secondary damage, which are the biochemical consequences of the first damage. Recently, the role that peripheral organs play in the progression of secondary damage in the central nervous system has been the focus of research worldwide, however, the way in which different peripheral organs communicate in the path physiology of TBI has not yet been established. In the sports environment, recurrent concussions (RC), especially in contact sports, are hardly new. The concern is its recurrence, which leaves the brain vul-nerable to damage that leads to significant cognitive changes. Although attention is focused on the func-tioning of the brain, studies that assess the vulnerability window of RC in peripheral organs are still incipient. Thus, the work aims to review and investigate the effects of TBI and RC associated with the practice of physical exercise in the intestine, spleen and cerebral cortex of rats. To this end, in addition to a literature review on the subject, 30-day-old male Wistar rats will be divided into 4 groups (Sedentary Control, Sedentary Concussion, Exercise Control and Concussion Exercise), submitted to a five-week swimming protocol, where twice a week will suffer a concussion by the weight-drop model (54g to 71cm), totaling ten concussions. Seven days after the last swimming and concussion session, the animals will be euthanized, the proximal colon (PC) will be used for the analysis of the oxidative, nitrosactive, inflammatory state. Parameters related to the cholinergic anti-inflammatory system were evaluated in both the spleen and the PC, and the expression of GFAP was verified in the cerebral cortex. In PC, RC induced lipoperoxidation, decreased antioxidant capacity and increased acetyl cholinesterase (AChE) activity, as well as α7 nAChR expression. Such alterations are not induced by nitrosative damage, since there was no alteration in the expression of iNOS and 3-NT. The swimming protocol limited the changes induced by RC and proved to be effective in increasing the activity of the enzyme Na+/K+ -ATPase, as well as normalizing the activity of AChE and induced increased expression of 5HT4R. The increased expression of Nrf2 in the Concussion exercise group may be behind the maintenance of the antioxidant capacity and the limitation of lipid peroxidation in this group. Changes in PC occur without astrogliosis in the cortex, and changes in the expression of nAChRα7 and Nrf2 seen in PC are not repeated in the spleen, dissociating the response of different organs to the RC and exercise protocol. We conclude that the swimming protocol limits the changes induced by RC, indicating a decrease in the time window of vulnerability, at the intestinal level, to a second concussion.